Measurement of Company Profits through Musharaka Financing Profit Sharing and Murabahah Margin - Chaerun Nisa (Khazanah Sosial, 2020)
The purpose of this study was to determine the effect of revenue sharing for musyarakah financing on company profits found at PT. Bank Muamalat Indonesia, then to determine the effect of murabaha financing margins on company profits at PT. Bank Muamalat Indonesia, and to find out how much influence the revenue sharing revenue from musyarakah financing also income from murabahah financing margins on company profits at PT. Bank Muamalat Indonesia. The method used in this research is descriptive verification analysis method using a quantitative approach that is analyzed partially and simultaneously. The results of this study indicate that the statistical test of revenue sharing results musyarakah on corporate profits shows the results of the coefficient of determination of 0.6%, the statistical test of murabaha financing margins on company profits shows the results of the coefficient of determination of 1.4%, a statistical test between income-sharing financing Musharaka and murabahah financing margins on company profits show the results of the coefficient of determination that is equal to 5.4%, the remaining 94.6% which is likely to be influenced by other factors not discussed and examined in this study.Â